Pengembangan Bahan Ajar Adaptif Berbasis Artificial Intelligence untuk Meningkatkan Kualitas Pembelajaran Sekolah Dasar di Sekolah Alam Ananda Mandiri - Ratri Wikaningtyas; Nurhayati Nurhayati; Sigit Arvianto; Handoko Aji Wardana; Istiqomah Istiqomah; Ririn Hestiningtyas; Imam Budi Prasetyo (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The need for learning materials that can adapt to students’ abilities and characteristics has made the development of AI-based adaptive learning resources increasingly important in elementary education. However, limited digital literacy and high workloads among teachers hinder optimal implementation. This Community Service Program aimed to enhance the competencies of teachers at Sekolah Alam Ananda Mandiri Slawi through workshops, guided practice, and hands-on development of AI-supported adaptive materials. The method included preparation, conceptual presentation, technology demonstration, guided practice, pre–post evaluation, and follow-up support. The results showed a significant improvement, with teachers’ competence in the “good” category increasing from 22.5% to 82.5%, and all participants (100%) successfully producing at least one adaptive module and one deep-learning-based material component. Furthermore, 92% of participants reported that the program greatly improved their digital literacy and pedagogical understanding. Thus, this activity effectively strengthened teachers’ competencies and provided a strong foundation for the sustainable integration of AI-based adaptive learning materials in elementary classrooms.